The Effect of Audit Tenure, Audit Fee, Auditor Specialization, Auditor Reputation and Firm Size on Audit Quality - Damayanti, Risma Alfian; Trisnawati, Rina (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study seeks to examine the impact of audit tenure, audit fees, auditor specialisation, auditor reputation, and the size of accounting firms on the quality of audits in manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2021. Recent public perceptions of audit quality have been influenced by the discovery of violations within clients' accounting systems, which have been reported in audited financial statements. These violations involve public accountants, highlighting the importance of the manufacturing sector to the Indonesian economy. This sector, with its high volume of transactions and complexity compared to other sectors, necessitates further research to identify factors that can influence audit quality, particularly in manufacturing companies. In this study, audit tenure, audit fees, auditor specialisation, auditor reputation, and the size of the accounting firm are considered as independent variables, with audit quality as the dependent variable. This research is conducted with a commitment to rigour and thoroughness, reflecting the standards expected of seasoned researchers in the field. Methodology: This study utilises SPSS software version 27 for hypothesis testing, descriptive statistical analysis, and logistic regression analysis. Secondary data were gathered from 193 manufacturing companies listed on the Indonesian Stock Exchange, spanning a four-year observation period. The sample was selected using a sampling method, yielding data from 168 companies. Results: The research findings indicate that audit tenure and auditor specialisation significantly influence audit quality. Conversely, audit fees, auditor reputation, and firm size do not have a significant impact on audit quality. Applications/Originality/Value: The study underscores the importance of specialisation in client selection for public accounting firms aiming to enhance audit quality. This research contributes original insights of value to the field, particularly for practitioners seeking to improve audit processes and outcomes.